DIAGNOSTIC VALUE OF CLINICAL AND LABORATORY IMMUNOLOGICAL SIGNS OF INFECTIOUS MONONUCLEOSIS - I. P. Baranova; D. Yu. Kurmaevа; O. N. Lesina (LLC "Diagnostics and Vaccines", 2015)
For evaluation of importance of each of the leading clinical and laboratory signs of infectious mononucleosis the authors conducted a statistical analysis of the data from 280 patients aging from 10 months to 34 years of age. The analysis was carried out with the use of nonparametric statistical method analysis (ranking analysis of variance and concordance by M. Kendall). Three basic clinic pathogenetic syndromes (lymphoproliferative - tonsillar, lymphoproliferative - parenchymal, lymphostasis ectodermal). Characteristics of laboratory syndrome of immune imbalance are given. An algorithm for the diagnosis of infectious mononucleosis with the inclusion of clinical, laboratory, instrumental, immunological studies is suggested.